Analiza pogajalskega sporazumevanja - Schlamberger Brezar, Mojca (Jezik in slovstvo, 1998)
Negotiation is defined as an exchange leading to an agreement, which makes it a general component of communication. The article describes objects of negotiation and possible negotiating strategies as determined on the basis of discourse analysis. These description are followed by examples of authentic negotiation.
Keywords: Slovene; slovenščina; sociolinguistics; sociolingvistika; sporazumevanje; pogajanje